Arah Masa Depan Rekam Medis Elektronik dalam Era Kesehatan Digital: Literature Review : Arah Masa Depan Rekam Medis Elektronik dalam Era Kesehatan Digital: Literature Review - I Gusti Agung Ngurah Putra Pradnyantara; Harinto Nur Seha; Nisa Nur Kusuma (Program Studi D3 Rekam Medis dan Informasi Kesehatan, 2025)
Electronic Medical Records (EMR) have become one of the key pillars of digital health transformation, particularly in improving documentation efficiency, quality of care, and patient data integration. However, the implementation of EMR in various countries, including Indonesia, still faces several challenges such as limited infrastructure, user resistance, data standardization issues, and information security concerns. This study is a scoping review aimed at mapping the challenges and strategies of EMR implementation based on relevant literature from the past ten years. Articles were searched through PubMed, Scopus, and Google Scholar using the keywords “electronic medical record,” “implementation challenges,” and “strategies.” The review findings indicate that the main barriers to EMR implementation include technical factors (interoperability, infrastructure costs), human factors (digital literacy of healthcare professionals, resistance to change), and organizational factors (management support, policies, and regulations). Strategies frequently recommended in the literature include continuous training, early stakeholder engagement in the planning phase, clear national policies, and strengthening data security and privacy. This study provides a comprehensive overview of the dynamics of EMR implementation and can serve as a basis for decision-making by healthcare managers and policymakers in supporting digital health transformation. Keywords: electronic medical record, implementation, challenges, strategies, scoping